PSYCHOLOGICAL CHARACTERISTICS OF THE FORMATION OF MILITARY IMAGINATIONS IN HIGH SCHOOL STUDENTS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
In this article, comments on forming the qualities of vigilance and awareness in the behavior of teenagers, improving the methodical-methodical system of creating a positive social, spiritual, psychological environment in the family and in the field of education, and forming military imaginations in high school students , at the same time, the results of the research on the influence of the activities of the pedagogue and the pedagogical group on teenagers are presented